Low-impedance adhesion ultrathin cellulose membrane as well as preparation method and application thereof

Through the methods of metal ions bonding and cellulose and ionic liquid adjustment, the problems of insufficient environmental pollution and formability of epidermal electronic materials in the prior art are solved, and a low-impedance ultra-thin cellulose film suitable for health monitoring and medical treatment are prepared. , good contact with biological tissues and high signal-to-noise ratio signal-to-noise ratio signal-to-noise ratio signal-to-noise ratio signal-to-noise ratio signal-to-noise ratio signal-to-noise ratio signal-to-noise ratio.

CN119241878APending Publication Date: 2025-01-03TIANJIN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411407517.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Most of the existing epidermal electronic materials are organic synthetic materials, which have the risk of environmental pollution and are difficult to achieve soft, thin, and have good form-retaining and low impedance cellulose membranes, which affect their application in the fields of health monitoring and medical care.

Method used

The metal ions released by the metal material are bonded to dissolved cellulose, and after preliminary molding, they are regenerated in the regenerated liquid, and the hydrogen bond between the cellulose segments is adjusted in combination with the ionic liquid to prepare super-retaining properties and low impedance Thin cellulose membrane.

Benefits of technology

The prepared ultra-thin cellulose membrane can better contact with biological tissue, reduce tissue damage and rejection, have excellent stability and high sensitivity, and is suitable for electronic skin and medical diagnosis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241878A_ABST
    Figure CN119241878A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a low-impedance adhesion ultrathin cellulose membrane. The preparation method comprises the following steps: S1, dissolving cellulose; s2, preparing a metal cellulose film; s3, regenerating with a regenerant; after metal ions released by a metal material and cellulose dissolved in the cellulose are bonded and preliminarily formed, the ultrathin cellulose membrane with good shape retention and low impedance is obtained through regeneration in a regeneration liquid agent. The invention relates to a low-impedance adhesion ultrathin cellulose membrane, which has a thin and flexible structure, so that the cellulose membrane can be in better contact with biological tissues, and the risk of tissue damage and rejection reaction is reduced; metal complexing enables epidermal electrons to have excellent stability; the ultrathin cellulose membrane has the advantages of high sensitivity, good signal-to-noise ratio, low impedance and good fit with the skin, and has a great application prospect in the fields of electronic skin, medical diagnosis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cellulose material film preparation, and in particular relates to a low-impedance adhesion ultra-thin cellulose film and a preparation method and application thereof. Background Art

[0002] Epidermal electronics, that is, wearable electronic devices attached to the epidermis, are a new form of wearable electronics developed in recent years. Different from rigid traditional electronic devices, they are comfortable to wear, capture physiological signals with high fidelity and reliability, and have the ability of long-term, real-time monitoring. They have shown great advantages in many fields such as health monitoring, human-computer interaction, electronic skin, motion monitoring, and clinical medicine.

[0003] However, the development of epidermal electronics still faces challenges. In order to avoid the discomfort of being heavy when worn, epidermal electronics should be soft and thin enough. At the same time, the shape retention and interfacial adhesion of epidermal electronics are crucial to eliminating motion artifacts and improving the accuracy of signal collection. Existing epidermal electronics are mostly made of organic synthetic materials, which usually require the use of organic substances such as organic solvents, which may cause a certain degree of pollution to the environment and are not conducive to sustainable development and environmental protection.

[0004] From the perspective of sustainable development, biodegradable cellulose, which is abundant in nature, is one of the most suitable materials for making epidermal electronics. Cellulose is a cellulose ultra-thin film made of biomass materials. Its thin and flexible structure enables it to better contact with biological tissues, reducing the risk of tissue damage and rejection reactions. Secondly, metal complexation gives the electrode excellent stability and durability. Moreover, biomass epidermal electrodes have the characteristics of reversible adhesion, can easily interact with biological systems, and can be removed in a controllable manner, reducing interference with biological tissues. Therefore, it is a major challenge to make a cellulose film with good shape retention for application in the field of epidermal electronics. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a low-impedance adhesive ultra-thin cellulose film and a preparation method and application thereof.

[0006] The present invention solves the technical problem by the following technical solutions:

[0007] A method for preparing a low-impedance adhesion ultra-thin cellulose film, wherein the method utilizes metal ions released by a metal material to bond with cellulose in dissolved cellulose to form a preliminary shape, and then regenerates the cellulose in a regeneration liquid to obtain an ultra-thin cellulose film with good shape retention and low impedance; the steps of the method are:

[0008] S1, dissolving cellulose: using an alkaline solvent to dissolve absolutely dry cellulose to obtain transparent cellulose solutions with different solid contents;

[0009] S2, preparation of metal cellulose film: evenly spraying metal powder on the surface of the transparent cellulose solution of S1, so that the metal powder reacts with the alkaline solvent in the transparent cellulose solution to release metal ions, and the metal ions complex the cellulose, and the cellulose is initially regenerated into a film;

[0010] S3, regeneration with regeneration agent: the film initially regenerated in S2 is peeled off from the upper metal layer and transferred to the regeneration agent to wash away the solvent, thereby increasing the degree of regeneration and obtaining a low-impedance adhesive cellulose film with electrical conductivity and shape retention.

[0011] Furthermore, the S3 is transferred to the regeneration agent, and the washed film is transferred to the ion solution to adjust the number of hydrogen bonds between the cellulose in the film and reduce the modulus.

[0012] Moreover, the ionic solution of S3 is one or more of 1-ethyl-3-methylimidazolium chloride ([EMIM]Cl), 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), and 1-allyl-3-methylimidazolium chloride ([AMIM]Cl).

[0013] Furthermore, the condition for the ionic liquid to adjust the number of hydrogen bonds between the film cellulose is room temperature, and the adjustment time is 30 minutes to 60 minutes.

[0014] Moreover, the alkaline solvent of S1 is a solvent that has no derivative reaction when dissolving cellulose and directly destroys the hydrogen bond structure. The alkaline solvent is one or more of NaOH / urea (thiourea) / water, LiOH / urea (thiourea) / water, NaOH / water, and KOH / urea (thiourea) / water.

[0015] Moreover, the absolute dry cellulose in S1 is one or more of cotton colloid and cotton linters, and the concentration of the obtained transparent cellulose solution is 0.5wt% to 10wt%.

[0016] Moreover, the metal powder of S2 is one or more of copper powder, silver powder, gold powder and iron powder; the time for the metal powder of S2 to react with the alkaline solvent in the transparent cellulose solution is 2 to 10 minutes.

[0017] Moreover, the regeneration agent of S3 is one or more of ethanol, water, and glycerol.

[0018] An ultra-thin cellulose film is prepared by adopting the preparation method.

[0019] A low-impedance adhesive ultrathin cellulose film for use in electronic skin.

[0020] The advantages and beneficial effects of the present invention are:

[0021] The preparation method of the present invention utilizes metal ions released by metal materials to bond with cellulose segments in dissolved cellulose for initial forming, and then regenerates the obtained ultrathin cellulose membrane in a regeneration liquid, and then adjusts the hydrogen bonds between the cellulose segments by ionic liquid to obtain an ultrathin cellulose membrane with good shape retention and low impedance; the ultrathin cellulose membrane prepared by the present invention has a thin and flexible structure, which enables it to better contact with biological tissues, reducing the risks of tissue damage and rejection reactions; metal complexation enables the epidermal electronics to have excellent stability; the ultrathin cellulose membrane provided by the present invention has high sensitivity, good signal-to-noise ratio, low impedance, and good fit with the skin, and has great application prospects in the fields of electronic skin and medical diagnosis. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a flow chart of the preparation method of the present invention;

[0023] Figure 2 This is a graph showing the XPS analysis results of the ultra-thin cellulose film obtained in Example 1 of the present invention;

[0024] Figure 3 This is an electron microscope thickness image of the ultra-thin cellulose film obtained in Example 1 of the present invention;

[0025] Figure 4 This is a comparison diagram of the impedance of the ultra-thin cellulose membrane prepared in Example 1 of the present invention and the commercial electrode;

[0026] Figure 5 This is a comparison chart of the ECG signals collected by the commercial electrode and the ultra-thin cellulose membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0028] Example 1

[0029] A method for preparing a low-impedance adhesive ultra-thin cellulose film, the innovation of which lies in: the steps of the preparation method are:

[0030] 1. A LiOH (4.5 wt%) / urea (15 wt%) aqueous solution was precooled to -12°C; the absolutely dry cellulose was ground into a cotton-like state by a grinder; 0.5 g of the dried cellulose was added to 100 g of the LiOH / urea aqueous solution to obtain a transparent cellulose solution with a concentration of 0.5 wt%.

[0031] 2. Pour 30g of 0.5wt% cellulose solution into a 100mm*100mm mold, evenly spray 0.2g of copper powder on the surface, and let it stand for 2min; immerse the entire mold containing copper powder and dissolved cellulose in water and let it stand for 2min; the metal powder and the initially formed cellulose membrane are located on the water surface, and the initially formed cellulose membrane and the metal powder and copper powder are peeled off using a glass rod to obtain a initially formed cellulose membrane.

[0032] 3. Transfer the initially formed cellulose membrane into regeneration agent water and regenerate for 48 hours to obtain an environmentally stable cellulose membrane.

[0033] 4. After 48 hours of regeneration, the cellulose membrane was placed in the ionic liquid 1-butyl-3-methylimidazolium chloride and allowed to stand at 40°C for 30 minutes to form a soft cellulose membrane with good shape retention.

[0034] Example 2

[0035] A method for preparing a low-impedance adhesive ultra-thin cellulose film, the innovation of which lies in: the steps of the preparation method are:

[0036] 1. A LiOH (4.5 wt%) / urea (15 wt%) aqueous solution was precooled to -12°C; the absolutely dry cellulose was ground into a cotton-like state by a grinder; 1 g of the dried cellulose was added to 100 g of the LiOH / urea aqueous solution to obtain a transparent cellulose solution with a concentration of 1 wt%.

[0037] 2. Pour 30g of 1wt% cellulose solution into a 100mm*100mm mold, evenly spray 0.2g of copper powder on the surface, and let it stand for 2min; immerse the entire mold containing copper powder and dissolved cellulose in water and let it stand for 2min; the metal powder and the initially formed cellulose membrane are located on the water surface, and use a glass rod to peel off the initially formed cellulose membrane from the metal powder and copper powder to obtain a initially formed cellulose membrane.

[0038] 3. Transfer the initially formed cellulose membrane into regeneration agent water and regenerate for 48 hours to obtain an environmentally stable cellulose membrane.

[0039] 4. After 48 hours of regeneration, the cellulose membrane was placed in the ionic liquid 1-butyl-3-methylimidazolium chloride and allowed to stand at 40°C for 30 minutes to form a soft cellulose membrane with good shape retention.

[0040] Example 3

[0041] A method for preparing a low-impedance adhesive ultra-thin cellulose film, the innovation of which lies in: the steps of the preparation method are:

[0042] 1. A LiOH (4.5 wt%) / urea (15 wt%) aqueous solution was precooled to -12°C; the absolutely dry cellulose was ground into a cotton-like state by a grinder; 0.5 g of the dried cellulose was added to 100 g of the LiOH / urea aqueous solution to obtain a transparent cellulose solution with a concentration of 0.5 wt%.

[0043] 2. Pour 30g of 0.5wt% cellulose solution into a 100mm*100mm mold, evenly spray 0.2g of copper powder on the surface, and let it stand for 10min; immerse the mold containing copper powder and dissolved cellulose in water as a whole, and let it stand for 10min; the metal powder and the initially formed cellulose membrane are located on the water surface, and a glass rod is used to peel off the initially formed cellulose membrane from the metal powder and copper powder to obtain a initially formed cellulose membrane.

[0044] 3. Transfer the initially formed cellulose membrane to the regeneration agent water and regenerate for 48 hours to obtain an environmentally stable cellulose membrane

[0045] 4. After 48 hours of regeneration, the cellulose membrane was placed in the ionic liquid 1-butyl-3-methylimidazolium chloride and allowed to stand at 40°C for 30 minutes to form a soft cellulose membrane with good shape retention.

[0046] Example 4

[0047] A method for preparing a low-impedance adhesive ultra-thin cellulose film, the innovation of which lies in: the steps of the preparation method are:

[0048] 1. A LiOH (4.5 wt%) / urea (15 wt%) aqueous solution was precooled to -12°C; the absolutely dry cellulose was ground into a cotton-like state by a grinder; 0.5 g of the dried cellulose was added to 100 g of the LiOH / urea aqueous solution to obtain a transparent cellulose solution with a concentration of 0.5 wt%.

[0049] 2. Pour 30g of 0.5wt% cellulose solution into a 100mm*100mm mold, evenly spray 0.2g of copper powder on the surface, and let it stand for 10min; immerse the mold containing copper powder and dissolved cellulose in water as a whole, and let it stand for 10min; the metal powder and the initially formed cellulose membrane are located on the water surface, and a glass rod is used to peel off the initially formed cellulose membrane from the metal powder and copper powder to obtain a initially formed cellulose membrane.

[0050] 3. The initially formed cellulose membrane is transferred to the regeneration agent ethanol and regenerated for 48 hours to obtain an environmentally stable cellulose membrane.

[0051] 4. After 48 hours of regeneration, the cellulose membrane was placed in the ionic liquid 1-butyl-3-methylimidazolium chloride and allowed to stand at 40°C for 30 minutes to form a soft cellulose membrane with good shape retention.

[0052] The ultra-thin cellulose films prepared by the above examples have relatively small differences in thickness and shape retention, so Example 1 is used for analysis.

[0053] Figure 2 These are the XPS analysis results of the ultrathin cellulose membrane obtained in Example 1 of the present invention, wherein (a) is the C1S fitting XPS graph of the pure fiber membrane and the ultrathin cellulose membrane, from which it can be observed that the CO proportional area of ​​the ultrathin cellulose is reduced, indicating the formation of a CO complex, and (b) is the Cu2p fitting XPS graph of the ultrathin cellulose, from which the characteristic peaks of copper ions can be observed, indicating that copper ions act on the cellulose structure.

[0054] Figure 3 The thickness scanning electron microscope image of the ultra-thin cellulose prepared by implementing Example 1 of the present invention shows that the thickness is 3um, indicating the thin physical structure of the cellulose membrane, which ensures that the film as epidermal electronics can better contact with biological tissues, reducing the risk of tissue damage and rejection reaction. Figure 4 The impedance obtained from the cellulose membrane test was shown to be lower than that of commercial electrodes, indicating that the cellulose membrane has good contact with the skin and good signal conductivity, which will be conducive to obtaining high-quality bioelectric signals and reducing signal fluctuations caused by impedance changes during the measurement process, thereby improving the reliability of long-term monitoring. Figure 5 The good ECG signals collected by using ultrathin cellulose membrane as epidermal electrodes were demonstrated.

[0055] In summary, the ultrathin cellulose film prepared by the present invention has a thin and flexible structure, which enables it to better contact with biological tissues, reducing the risk of tissue damage and rejection reactions; the good shape retention and low impedance characteristics make the cellulose film have great application prospects in the fields of electronic skin and medical diagnosis.

[0056] Although the embodiments and drawings of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.

Claims

1. A method for preparing a low-impedance adhesion ultra-thin cellulose film, characterized in that: The method utilizes metal ions released by the metal material to bond with cellulose in the dissolved cellulose to form a preliminary shape, and then regenerates the cellulose in the regeneration liquid to obtain an ultra-thin cellulose film with good shape retention and low impedance; the steps of the method are: S1, dissolving cellulose: using an alkaline solvent to dissolve absolutely dry cellulose to obtain transparent cellulose solutions with different solid contents; S2, preparation of metal cellulose film: evenly spraying metal powder on the surface of the transparent cellulose solution of S1, so that the metal powder reacts with the alkaline solvent in the transparent cellulose solution to release metal ions, and the metal ions complex the cellulose, and the cellulose is initially regenerated into a film; S3, regeneration with regeneration agent: the film initially regenerated in S2 is peeled off from the upper metal layer and transferred to the regeneration agent to wash away the solvent, thereby increasing the degree of regeneration and obtaining a low-impedance adhesive cellulose film with electrical conductivity and shape retention.

2. The method for preparing a low-impedance adhesion ultra-thin cellulose film according to claim 1, characterized in that: The S3 is transferred to the regeneration agent, and the washed film is transferred to the ion solution to adjust the number of hydrogen bonds between the film cellulose and reduce the modulus.

3. The method for preparing a low-impedance adhesion ultra-thin cellulose film according to claim 2, characterized in that: The ionic solution of S3 is one or more of 1-ethyl-3-methylimidazolium chloride ([EMIM]Cl), 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), and 1-allyl-3-methylimidazolium chloride ([AMIM]Cl).

4. The method for preparing a low-impedance adhesion ultra-thin cellulose film according to claim 2, characterized in that: The condition for the ionic liquid to adjust the number of hydrogen bonds between the film cellulose is room temperature, and the adjustment time is 30 minutes to 60 minutes.

5. The method for preparing a low-impedance adhesion ultra-thin cellulose film according to claim 1, characterized in that: The alkaline solvent of S1 is a solvent that has no derivatization reaction when dissolving cellulose and directly destroys the hydrogen bond structure. The alkaline solvent is one or more of NaOH / urea (thiourea) / water, LiOH / urea (thiourea) / water, NaOH / water, and KOH / urea (thiourea) / water.

6. The method for preparing a low-impedance adhesion ultra-thin cellulose film according to claim 1, characterized in that: The absolute dry cellulose in S1 is one or more of cotton colloid and cotton linters, and the concentration of the obtained transparent cellulose solution is 0.5wt% to 10wt%.

7. The method for preparing a low-impedance adhesion ultra-thin cellulose film according to claim 1, characterized in that: The metal powder of S2 is one or more of copper powder, silver powder, gold powder and iron powder; the time for the metal powder of S2 to react with the alkaline solvent in the transparent cellulose solution is 2 to 10 minutes.

8. The method for preparing a low-impedance adhesion ultra-thin cellulose film according to claim 1, characterized in that: The regeneration agent of S3 is one or more of ethanol, water and glycerol.

9. A low impedance adhesive ultra-thin cellulose film, characterized in that: The preparation method is as described in any one of claims 1 to 8.

10. Use of the low-impedance adhesive ultra-thin cellulose film according to claim 9 in electronic skin.

Citation Information

Cited By

  • Ultrathin biomass conductive film and in-situ rapid preparation method and application thereof

    CN120842989A